Use of the Roche LightCycler ® 480 system in a routine laboratory setting for molecular diagnosis of opportunistic viral infections: Evaluation on whole blood specimens and proficiency panels - Deback, Claire; Géli, Julienne; Aït-Arkoub, Zaïna; Angleraud, Francis; Gautheret-Dejean, Agnès; Agut, Henri; Boutolleau, David (Journal of virological methods, 2009)
The Roche LightCycler ® 480 (LC480) system was evaluated for quantitative molecular diagnosis of opportunistic viral infections caused by human cytomegalovirus (HCMV), Epstein–Barr virus (EBV), human herpesvirus 6 (HHV-6) and BK virus (BKV), in comparison with “in-house” real-time PCR assays. A total of 253 whole blood specimens obtained from transplant recipients were tested. Both the “in-house” and the LC480 methods were highly correlated (Spearman correlation coefficient Rho ≥ 0.85; p < 0.0001) with an excellent overall qualitative agreement (90.5%) and no significant quantitative difference between both techniques for the four viruses tested. The accuracy of the LC480 protocols were confirmed further by the results obtained with the 44 samples from the Quality Control for Molecular Diagnosis (QCMD) 2008 proficiency panel. The LC480 system constitutes a suitable and versatile real-time PCR platform in a routine laboratory setting for the diagnosis and monitoring of opportunistic viral infections in transplant recipients, by measuring HCMV, EBV, HHV-6, and BKV loads in whole blood samples.